PROFIL SIKAP ILMIAH MAHASISWA CALON GURU FISIKA PADA PELAKSANAAN PRAKTIKUM RANGKAIAN LISTRIK SEARAH - Citra Asmara Dewi; Abidin Pasaribu; Saparini Saparini; Widya Rahmatika Rizaldi (Vidya Karya, 2022)
The research aimed to analyse the scientific attitude profile of prospective physics teacher students in the Physics Experiment II course for Direct Electric Circuits. This research is qualitative research with a descriptive method. The research subjects are students of the Physics Education Study Program, Sriwijaya University, in the academic year 2021/2022, for the Palembang class. The selection of research samples using a purposive sampling technique for 25 students. The data collection techniques used in this study were observation, self-assessment questionnaires, peer-to-peer assessment questionnaires, and unstructured interviews. Each questionnaire contains 25 statements with four answer categories to produce polytomy data. The data analysis technique of this research uses the Rasch model with the help of the Winstep application. The results of the study showed that the scientific attitude of curiosity was 83.33 in very good category; the honest scientific attitude of 58.33 category enough; the scientific attitude of critical thinking is 75.33 good category; the scientific attitude of cooperation is 83.33 very good category; the scientific attitude of the discipline of 100 categories is very good; and a thorough scientific attitude of 100 very good categories. The causes of low honest scientific attitude in students are caused by low self-confidence and errors in understanding and concluding statements.Penelitian bertujuan menganalisis profil sikap ilmiah mahasiswa calon guru fisika pada mata kuliah Praktikum Fisika Dasar II materi Rangkaian Listrik Searah. Penelitian ini merupakan penelitian kuantitatif dengan metode deskriptif. Subjek penelitian yaitu Mahasiswa Program Studi Pendidikan Fisika Universitas Sriwijaya tahun akademik 2021/2022 kelas Palembang. Adapun pemilihan sampel penelitian menggunaka teknik purposive sampling kepada 25 orang mahasiswa. Teknik pengumpulan data penelitian ini menggunakan observasi, angket penilaian diri, angket penilaian antar teman, dan wawancara tidak terstruktur. Angket masing-masing memuat 25 pernyataan dengan 4 kategori jawaban sehingga menghasilkan data politomi. Analisis data dilakukan menggunakan statistik deskriptif. Hasil penelitian menunjukkan sikap ilmiah rasa ingin tahu sebesar 83,33 kategori baik sekali; sikap ilmiah jujur sebesar 58,33 kategori cukup; sikap ilmiah berpikir kritis sebesar 75,33 kategori baik; sikap ilmiah kerjasama sebesar 83,33 kategori baik sekali; sikap ilmiah disiplin sebesar 100 kategori baik sekali; dan sikap ilmiah teliti sebesar 100 kategori baik sekali. Adapun penyebab rendahnya sikap ilmiah jujur pada mahasiswa disebabkan oleh rendahnya percaya diri dan terjadi kekeliruan dalam memahami serta menyimpulkan pernyataan.